PENGEMBANGAN GAME EDUKATIF TEBAK GAMBAR DAN HURUF UNTUK PERKEMBANGAN KOGNITIF ANAK USIA DINI - Sukarni Putri, Mulyana; Budiarti, Erna (Jurnal Tumbuh Kembang Anak Usia Dini, 2024)
This research aims to develop an educational game titled "Guess the Pictures and Letters" which is designed to improve the cognitive development of early childhood. This game was developed through a systematic approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the aim of identifying the needs of children in PAUD Annawawiyah Arrahmaniyah and implementing solutions that are in accordance with their cognitive development characteristics. This game is designed to improve logical thinking skills, imagination, and understanding of pictures and letters by using interactive and interesting elements such as drag-and-drop, puzzles, and choices that children can choose from. The research findings indicate that the educational guessing game for images and letters that has been developed has been tested and validated by experts, demonstrating that this game has good quality and is suitable for use by children aged 4-5 years in developing their cognitive abilities The validation results confirm that this game can be accessed both individually and in groups, and can be integrated into existing curricula Furthermore, out of the 10 subjects tested, the majority fell into the category of Developing as Expected (40%), followed by Starting to Develop (30%), Developing Very Well (20%), and Not Developing (10%) Subject-02 and Subject-06 achieved the highest scores, while Subject-09 had the lowest score. The conclusion drawn from this research is that the development of educational games for guessing images and letters has proceeded systematically and has identified relevant needs for enhancing logical thinking, imagination, and understanding of images and letters in young children This study proves that educational games can be an effective tool in improving the cognitive development of young children.